Comparative study on consumers’ choice behaviors in selecting pork in rational and irrational scenarios - Xu, Lingling; Yu, Meidan; Chen, Xiujuan (Frontiers in Psychology, 2022)
To better understand the purchasing decision-making process of humane pork, and examine the internal relationship between consumers’ preferences in rational consumption and irrational decoy scenarios, 405 consumers in Wuxi City, Jiangsu Province, and China were surveyed. Attributes were set for breeding time, breeding mode, diet cleanliness label, and price, and the first three among them reflect animal welfare conditions. The results show that in the rational consumption scenarios, consumers pay the most attention to the price attribute, followed by the attribute of diet cleanliness label, breeding mode, and breeding time. In the irrational decoy scenarios, consumers are most likely to be affected by the attribute decoy of diet cleanliness label, which have the utility of avoiding food safety risks. In addition, the decoy effect triggered by the price attribute which owned the highest degree of rational preference among consumers is also substantially higher, but lower than that of the diet cleanliness label attribute. The decoy effect caused by the breeding time attribute with the lowest degree of consumers’ rational preference is also the lowest. Therefore, the government should strengthen the publicity of the humane treatment of pigs before slaughter, and improve the certification and management system of pigs’ diet cleanliness. Besides, marketers are suggested to emphasis the product attributes that customer’s value the most in their advertising.